Greenness and pollution exposure predict corticosterone concentration in an urban songbird - Abolins-Abols, Mikus; Yeager, Ray; Turner, Jay; Smith, Ted; Bhatnagar, Aruni (Frontiers in Physiology, 2025)
Air pollution is known to negatively affect avian health, and some air pollutants have been suggested to drive changes in bird population size at a regional level. Although several studies have investigated the effect of air pollution on bird health, how air pollution exposure is associated with avian physiology at a local scale is not known. Moreover, the extent to which avian health may be affected by vegetation, which modulates pollutant deposition and dispersion, has not been assessed. Here we combine high-resolution mapping of major air pollutants (NO2 and ultrafine particles) and vegetation types with dense spatial sampling of American robins, an urban exploiter, to ask how air pollution exposure, vegetation, and their interaction predict baseline corticosterone and bird condition. The relationships between environmental variables and physiological metrics were assessed at various distances from the capture location. We found that elevated air NO2 concentration is associated with higher baseline corticosterone levels within 500 m of the capture location. Vegetation did not modulate the relationship between corticosterone and NO2. We found sex-dependent relationships between greenness, corticosterone, and body weight. Within 20 m from the capture locations female corticosterone showed negative relationship with leaf area index, while female body weight was positivity related to the overall greenness. These relationships were absent in males. Collectively, the results of this study show that variations in air pollution and vegetation at a local intra-neighborhood scale predict fitness- and stress-related markers in an urban songbird.